FUNGSI DAN PERAN TRADISI MAPALUS DALAM MASYARAKAT MINAHASA, SULAWESI UTARA - la mansi (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Minahasa, North Sulawesi. This researchaims to describe the function and the role of Mappalus in maintainingsocial unity in Minahasa society. This uses qualitative method,where data was collected by interview and observation. Then data wasanalyzed by descriptive-qualitative.This research indicates that Minahasa people still use this Mappalusto construct their social relation. This tradition has five principles are:family affairs, working together, unity, democratization, and religious.The tradition has function in maintaining the unity and harmonizationamong the plural people at Minahasa. The tradition based on situotimou tumoutou, torang samua basudara, and kaihake sumaheke, itmeans that man was born to do humanization, man lives to give a lifefor another man, and man lives to respect another man.